Genetic and polygenic risk score analysis for Alzheimer's disease in the Chinese population. Issue 1 (5th August 2020) - Zhou, Xiaopu; Chen, Yu; Ip, Fanny C. F.; Lai, Nicole C. H.; Li, Yolanda Y. T.; Jiang, Yuanbing; Zhong, Huan; Chen, Yuewen; Zhang, Yulin; Ma, Shuangshuang; Lo, Ronnie M. N.; Cheung, Kit; et al.
Abstract: Introduction: Dozens of Alzheimer's disease (AD)‐associated loci have been identified in European‐descent populations, but their effects have not been thoroughly investigated in the Hong Kong Chinese population. Methods: TaqMan array genotyping was performed for known AD‐associated variants in a Hong Kong Chinese cohort. Regression analysis was conducted to study the associations of variants with AD‐associated traits and biomarkers. Lasso regression was applied to establish a polygenic risk score (PRS) model for AD risk prediction. Results: SORL1 is associated with AD in the Hong Kong Chinese population. Meta‐analysis corroborates the AD‐protective effect of the SORL1 rs11218343 C allele. The PRS is developed and associated with AD risk, cognitive status, and AD‐related endophenotypes. TREM2 H157Y might influence the amyloid beta 42/40 ratio and levels of immune‐associated proteins in plasma. Discussion: SORL1 is associated with AD in the Hong Kong Chinese population. The PRS model can predict AD risk and cognitive status in this population.